2008
DOI: 10.1088/1126-6708/2008/12/089
|View full text |Cite
|
Sign up to set email alerts
|

Center vortices as sources of Abelian dominance in pure SU(2) Yang-Mills theory

Abstract: We argue that in the infrared regime of continuum Yang-Mills theory, the possibility of a mass gap in the charged sector is closely associated with the center vortex sector. The analysis of the possible consequences of the ensembles of defects is done by showing that the description of center vortices and monopoles is naturally unified by means of a careful treatment of Cho decomposition. If on the one hand confinement is usually associated with monopole condensation in a compact abelian model, in this scenari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(65 citation statements)
references
References 78 publications
0
65
0
Order By: Relevance
“…The simplest case corresponds to the fundamental representation ⃗w ¼ ⃗w i , i ¼ 1; …; N [44], which will be considered from now on. In chains, pairs of center vortex branches are matched by monopoles [16,52,57]. In this case, we can writeS…”
Section: A Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simplest case corresponds to the fundamental representation ⃗w ¼ ⃗w i , i ¼ 1; …; N [44], which will be considered from now on. In chains, pairs of center vortex branches are matched by monopoles [16,52,57]. In this case, we can writeS…”
Section: A Chainsmentioning
confidence: 99%
“…Chains were visualized as magnetic defects of a local color frame in Ref. [57]. Their relation to the observability of surfaces attached to the quark loop was discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Some theoretical steps have already been taken in this direction. Monopoles, center vortices, as well as chains formed by them, can be accommodated as topological defects of different local bases in colour space [46]- [48]. Recently, we showed that ensembles of chains in 3D generate the effective model,…”
Section: Su (N ) → Z(n ) Dual Superconductor Modelsmentioning
confidence: 99%
“…In ref. [22], motivated by previous work on the description of chains in the continuum, using defects of a local Lie basis [39], an analysis of center strings interpolated by monopoles was presented, pointing to some physical consequences. In this regard, lattice calculations predict a rich spectrum of exotic mesons.…”
Section: Additional Physical Propertiesmentioning
confidence: 99%